Mixed Infections of Four Viruses, the Incidence and Phylogenetic Relationships of Sweet Potato Chlorotic Fleck Virus (Betaflexiviridae) Isolates in Wild Species and Sweetpotatoes in Uganda and Evidence of Distinct Isolates in East Africa - Tugume, Arthur K.; Mukasa, Settumba B.; Valkonen, Jari P. T. (PLoS ONE, 2016)
Viruses infecting wild flora may have a significant negative impact on nearby crops, and vice-versa. Only limited information is available on wild species able to host economically important viruses that infect sweetpotatoes (Ipomoea batatas). In this study, Sweet potato chlorotic fleck virus (SPCFV; Carlavirus, Betaflexiviridae) and Sweet potato chlorotic stunt virus (SPCSV; Crinivirus, Closteroviridae) were surveyed in wild plants of family Convolvulaceae (genera Astripomoea, Ipomoea, Hewittia and Lepistemon) in Uganda. Plants belonging to 26 wild species, including annuals, biannuals and perennials from four agroecological zones, were observed for virus-like symptoms in 2004 and 2007 and sampled for virus testing. SPCFV was detected in 84 (2.9%) of 2864 plants tested from 17 species. SPCSV was detected in 66 (5.4%) of the 1224 plants from 12 species sampled in 2007. Some SPCSV-infected plants were also infected with Sweet potato feathery mottle virus (SPFMV; Potyvirus, Potyviridae; 1.3%), Sweet potato mild mottle virus (SPMMV; Ipomovirus, Potyviridae; 0.5%) or both (0.4%), but none of these three viruses were detected in SPCFV-infected plants. Co-infection of SPFMV with SPMMV was detected in 1.2% of plants sampled. Virus-like symptoms were observed in 367 wild plants (12.8%), of which 42 plants (11.4%) were negative for the viruses tested. Almost all (92.4%) the 419 sweetpotato plants sampled from fields close to the tested wild plants displayed virus-like symptoms, and 87.1% were infected with one or more of the four viruses. Phylogenetic and evolutionary analyses of the 30-proximal genomic region of SPCFV, including the silencing suppressor (NaBP)- and coat protein (CP)-coding regions implicated strong purifying selection on the CP and NaBP, and that the SPCFV strains from East Africa are distinguishable from those from other continents. However, the strains from wild species and sweetpotato were indistinguishable, suggesting reciprocal movement of SPCFV between wild and cultivated Convolvulaceae plants in the field.
Keywords: Infections; Viruses; Phylogenetic Relationships; Sweet Potato Chlorotic Fleck Virus (Betaflexiviridae); Wild Species; Sweetpotatoes; Uganda; East Africa